Studi Literatur Review : Manajemen Infrastruktur - Farid Al Farizi; Mochammad Isa Anshori (Student Scientific Creativity Journal, 2024)
Infrastructure management is coordination between the physical work environment and employees and work in an organization to maintain the quality of an integrated work environment in operating, maintaining, improving and adapting through the organizational restructuring process so that employee contributions can be realized in achieving company goals. Strength in the form of commitment and individual strength is individual capital that is important for management. This shows that the organizational role of employee contributions as superior employees (store employees) creates intellectual capital through greater effort and hard work which is closely related to the creation of intellectual capital.